2004
DOI: 10.1079/bjn20041273
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of predicted body fat percentage from anthropometric methods and from impedance in university students

Abstract: The objective of the present study was to compare different methods for evaluating body fat percentage (BF%) (anthropometric methods and bioelectrical impedance analysis) in university students. Subjects were 653 healthy students whose mean age, body height, body weight and BMI were 21·1 (SD 2·5) years, 166·0 (SD 8·4) cm, 62·8 (SD 11·0) kg and 22·7 (SD 3·1) kg/m 2 , respectively. Results showed that BMI is a poor predictor of body fatness since the sensitivity was low in comparison with the reference method (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 35 publications
2
26
0
7
Order By: Relevance
“…29,43,44 The vague associations between physical activity and BMI may reflect a relatively poor specificity of BMI as a measure of overweight, which is particularly relevant in young, muscular men. This view is supported by other studies [45][46][47][48] and by data from dual-energy X-ray absorptiometry obtained for all 783 men (personal data, unpublished): when using a cutoff for overweight of 20% body fat, the specificity using WC was 92.0%, but only 77.9% for BMI. Hence, the prevalence of overweight in our study as defined by BMI (31.7%) is probably an over-estimate, which may explain the disagreement with the prevalence of overweight using WC (16.2%).…”
Section: Discussionsupporting
confidence: 56%
“…29,43,44 The vague associations between physical activity and BMI may reflect a relatively poor specificity of BMI as a measure of overweight, which is particularly relevant in young, muscular men. This view is supported by other studies [45][46][47][48] and by data from dual-energy X-ray absorptiometry obtained for all 783 men (personal data, unpublished): when using a cutoff for overweight of 20% body fat, the specificity using WC was 92.0%, but only 77.9% for BMI. Hence, the prevalence of overweight in our study as defined by BMI (31.7%) is probably an over-estimate, which may explain the disagreement with the prevalence of overweight using WC (16.2%).…”
Section: Discussionsupporting
confidence: 56%
“…The Brozek equation, originally developed for non-athletic young adult males, has subsequently been applied to different populations, including older adults (3). Although the study of the accuracy of these two equations has already been done in adults (18,19), in older people it remains to be seen which equation provides a more accurate transformation of BD in %BF.Therefore, the purpose of the present study is to identify which equation, Siri or Brozek, provides a more valid transformation of BD in %BF within older people. As DualEnergy X-ray Absorptiometry (DXA) is a well established reference method for the assessment of older individuals body composition (20,22), it was chosen as a criterion method.…”
mentioning
confidence: 95%
“…The Brozek equation, originally developed for non-athletic young adult males, has subsequently been applied to different populations, including older adults (3). Although the study of the accuracy of these two equations has already been done in adults (18,19), in older people it remains to be seen which equation provides a more accurate transformation of BD in %BF.…”
Section: Introductionmentioning
confidence: 99%
“…Gender differences in non normalized bioimpedance parameters (e.g., phase angle and resistive index) have been reported [11,12]. However we have demonstrated that these gender differences disappeared when normal-ized bioimpendance parameters (e.g., body capacitive index) were used [10].…”
Section: Introductionmentioning
confidence: 57%